2017
DOI: 10.22161/ijeab/2.6.19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selenium Nanoparticles on Growth, Biochemical Characteristics and Yield of Cluster Bean Cyamopsis tetragonoloba

Abstract: The present study deals with the impact of selenium nanoparticles on growth, biochemical characteristics and yield of Cluster bean Cyamopsis tetragonoloba grown for a period 60 days Sodium selenite and ascorbic acid was utilized for the synthesis of Selenium nanoparticles using precipitation method. Selenium nanoparticles were characterized by using SEM, EDAX, FTIR and XRD. Pot culture studies of cluster bean in different quantity of Selenium nanoparticles such as 0,100, 200, 300, 400 and 500mg for treatment T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 1 publication
7
26
0
Order By: Relevance
“…Previous studies showed that 10 mg L −1 of Cu NPs increased tomato growth and yield [21,22]. Likewise, in plants of Cyamopsis tetragonoloba, it was shown that the Se NPs increased the yield [29]. This could be due to the fact that Se NPs stimulate the formation of organs in plants [16,27].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed that 10 mg L −1 of Cu NPs increased tomato growth and yield [21,22]. Likewise, in plants of Cyamopsis tetragonoloba, it was shown that the Se NPs increased the yield [29]. This could be due to the fact that Se NPs stimulate the formation of organs in plants [16,27].…”
Section: Discussionmentioning
confidence: 98%
“…Also, El-Batal et al (2016) found an increase in chlorophyll content in Eruca sativa treated with selenium nanoparticles. Furthermore, Dong et al (2013) reported that selenium nanoparticles (10–50 ppm) significantly increased chlorogenic acid, chlorophyll and carotenoids by 200–400% of leaves of Lycium chinense L. Moreover, Ragavan et al, 2017 , Vijayarengan, 2013 ; and Sanghpriya Gautam (2015) reported that chemical selenium nanoparticles significantly increased the pigments in cluster beans.…”
Section: Discussionmentioning
confidence: 99%
“…pumpkins ( Cucurbita pepo ), potato, soybean and Canola ( Brassica napus L.) at a low concentration ( Djanaguiraman et al, 2005 , Germ et al, 2005 , Lyons et al, 2009 ), cluster bean ( Cyamopsis tetragonoloba L . ) ( Ragavan et al, 2017 ). On the same route, Hernández-Hernández et al (2019) found that tomato yield was increased by up to 21% with 10 mg L −1 of SeNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tomato, SeNPs improved the parameters of plant growth at low concentration (1 µM) [31]. Similarly, SeNPs at 400 mg improved the growth of the cluster bean [32].…”
Section: Improved Growth Of M Interexta Sproutsmentioning
confidence: 91%